Estimation of Non-Metallic Mineral Resources of Zeolite Commodities Using Aerial Photogrammetry, Vertical Electrical Sounding (VES), and Geological Mapping - Guntoro, Dono; Isniarno, Noor Fauzi; Mulyadi, Tommy; Alfarel, Muhammad Reyhand (UPT Publikasi Ilmiah UNISBA, 2025)
Geoelectricity is a method in geophysics that studies the nature of electric currents in the earth and how to detect them on the earth's surface. This detection includes measuring potential, current and electromagnetic differences that occur naturally or as a result of injecting current into the earth (Kanata, and Zubaidah., 2008). Azhar and Handayani (2004) have carried out laboratory scale modeling to measure the resistivity of several coal samples from the Air Laya Mine using the Wenner-Schlumberger configuration, with the rationale that the resistivity method has been widely used for various shallow seam exploration purposes. The resistivity method is a geophysical method used to measure the apparent resistivity of a medium. Measurements with the Schlumberger configuration use 4 electrodes, 2 current electrodes and 2 potential electrodes each. From the results of measuring the current and potential difference for each particular electrode distance, variations in the resistance value of each layer below the measuring point (sounding point) can be determined. Based on 1D Geoelectric activities in the investigation area, several conclusions were obtained, as follows. Based on the results of geological mapping in the investigation area, it was found that the rocks scattered in the investigation area were in the form of Volcanic Breccia and Tufa Breccia. Based on the results of field observations, it was found that the physical properties of hot water in the investigation area had a TDS value of 250 ppm, then had a temperature of 54° Celsius and an electrical conductivity of 983 μS/m. Based on the results of the 1D Geoelectric investigation, it was found that there are several interpreted lithologies, namely Top Soil which is at an average depth ranging from 0 meters to 6,598 meters with an average resistivity value of 27.18 ohms, then next is the Volcanic Breccia lithology which is at The average depth ranges from 6,598 meters to 11,461 meters with an average resistivity value of 4.28 ohms, then next is the lithological indication of Tufa Breccia which is at an average depth ranging from 11,561 meters to 18,683 meters with an average resistivity value of 9 .44 ohm and then the lithological indication in the form of sandstone which is at an average depth ranging from 18.683 meters to 27.566 meters with an average resistivity value of 15.83 ohm and an indication of marl lithology at a depth of 27.566 meters to 39.55 meters with a resistance value type of 21.08.